The Potential of Sargassum oligocystum Harvested From Persian Gulf for the Adsorption of Copper Ions From Aqueous Solutions - Bahman Ramavandi; Ahmad Ebrahimi; Seyed Enayat Hashemi; Samad Akbarzadeh; Ghorban Asgari (Hamadan University of Medical Sciences, 2015)
This study revealed the potential of a brown alga, Sargassum oligocystum, harvested from Persian Gulf for the Cu2+ adsorption from aqueous solutions. The adsorption kinetic and isotherm and the characteristics of the biomass prepared from S. oligocystum (BSO) were investigated. The BSO was a mesoporous adsorbent with Brunauer, Emmett, and Teller (BET) surface area, a total pore volume, and an average pore diameter of 0.487 m2/g, 1.423 cm3/g and 12.5 nm, respectively. Fourier transform infrared spectroscopy (FTIR) analysis showed that there were many active functional groups such as alcohol and phenol groups, carbonyl, ethers, and esters on the BSO. Batch tests demonstrated that the Langmuir isotherm model best represented the equilibrium data with maximum copper ions adsorption capacity of 8.23 mg/g. Pseudo-second-order kinetic model was found to satisfactory describe the adsorption process. BSO is an easy-prepared adsorbent and could be an option for the treatment of Cu2+-laden wastewaters.